Do cryptocurrencies and gold hedge against market risks? A wavelet coherence analysis of ASEAN+2 and G5 countries - Zheng, Alice Huong Yong; Rahim, Rossazana Ab; Jing, Amy Huong Yong (Asian Journal of Economic Modelling, 2026)
Stock market volatility, economic shocks, and geopolitical tensions have intensified recently, resulting in heightened uncertainty and disruptions in global financial markets with ASEAN+2 and G5. Identifying reliable hedging and safe haven assets is therefore critical for risk management. Moreover, effective hedging and safe haven strategies are important to reduce the risk of a portfolio for investors and help keep the market stable by lowering market contagion and boosting investor confidence. Therefore, this study examines the hedge and safe-haven properties of various cryptocurrencies, Bitcoin, Bitcoin Cash, Cardano, Chainlink, Dogecoin, Ethereum, Ripple, and Tron, and gold against stock markets in ASEAN+2 (Indonesia, Malaysia, Singapore, Thailand, Vietnam, China, and Russia) and G5 countries (France, Germany, Japan, the United Kingdom, and the United States) over the period 2017–2024. The findings, derived from wavelet coherence analysis, reveal that these properties are not uniform but vary significantly by market, investment horizon (particularly beyond 128 days), and period (e.g., during crises vs. stability). This study underscores the limitation of static correlation-based methods and highlights the importance of wavelet coherence in revealing short-, medium-, and long-term correlations that traditional methods may overlook. The results provide crucial insights for investors and policymakers to enhance financial stability through better anticipation of market dynamics.